PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KEJUJURAN SISWA KELAS XI SMK FARMASI IKASARI PEKANBARU T.P 2014 / 2015 - Ira Qamra Mahirah Qamra Mahirah; Rosmawati '; Raja Arlizon Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine the effect of counseling group about the increasing of students honesty class XI SMK Farmasi Ikasari Pekanbaru 2014/2015. This research was conducted in SMK Farmasi Ikasari Pekanbaru from March 2015 to Mei 2015. The method of this research was used experimental method and pattern is one group pre test and posttest. 116 students as research subject have low honesty and 30 from them as sample (simple random sampling).  The instrument to collect the data is used questionnaire by Guttman scale. Data analysis technique is used correlation statistic technique. The result of this research is counseling group have an effect to increasing of students honesty class XI SMK Farmasi Ikasari Pekanbaru 2014/2015. This is based on the result of analysis, calculation showed tcount > ttable (3.489 > 2,000). So it can be conclude that group counseling have an effect to increasing of students honesty with contribution 46% meanwhile 54% influenced by another factor from environment and students themselves. Keywords : The Effect Of Group Counseling, Honesty